INVESTIGATION OF THE ROLE OF SOCIAL MEDIA MARKETING IN INCREASING CONSUMERS' PURCHASE INTENTION IN BOTTELED DRINKING WATER - Hana Nuraini; Usep Suhud; Dewi Agustin Pratama Sari (Jurnal Riset Multidisiplin Edukasi, 2025)
The purpose of this study was to determine the effect of social media marketing, brand awareness, perceived value, and brand image on purchase intention of consumers of bottled drinking water. The research method used in this study is quantitative method by distributing questionnaires. Sampling using purposive sampling technique and obtained 250 respondents as a sample. This research was processsed using SPSS version 26.0 and SEM (Structural Equation Model) through AMOS to analyze and generate data from this study. The findings show that Brand Awareness, Perceived Value, Brand Image has positive and significant effect on Social Media Marketing. Social Media Marketing has positive and significant effect on Purchase Intention. Brand Awareness, Perceived Value, and Brand Image has no effect on Purchase Intention. This research provides important implications for management who need to improving their marketing strategy on social media to push the purchase intention of consumers.